Growth Performance of Hopea Odorata Roxb. and Mimusops Elengi L. Seedlings Under Soil Compaction, Water and Nutrient Stresses Experienced in the Urban Environment - Zainudin, Siti Rubiah (2000)
The urban environment has a variety of biological, chemical and physical stresses that can limit tree growth. Hopea odorata and Mimusops elengi are among the most common tree species planted in parks, along roadsides and highways in urban areas. The ability of these two species in adapting to the harsh urban environment is of interest. The objective of this study was to evaluate comparatively the differences in morphological and ecophysiological responses of these two species to soil compaction, water and nutrient stresses and how these differences could contribute to an understanding of the effects of environmental stress on plant growth. A higher reduction in the morphological and physiological growth of H. odorata seedlings occurred on encountering soil compaction and water stresses compared to M. elengi seedlings during the fIrst 3 months of treatment. The lower reduction in the morphological growth of M. elengi seedlings could be due to the higher amount of nutrient available in the leaves at the start of the experiment. However, as time progressed, the reduction in the morphological and physiological growth of M. elengi seedlings increased due to the impeded root system that reduced the uptake of water and nutrients necessary for subsequent growth. Root growth of H. odorata seedlings was significantly restricted under soil compaction of bulk density > 1.6 g/cm3 during the first 3 months of treatment but after 6 months an almost similar rate to the control was resumed until the end of the experiment. In contrast, root growth of M. elengi seedlings under high compaction levels (> 1.4 g/cm3) was still confined to the upper 20-cm compacted zone indicating that bulk densities of> 1 .4 glcm3 inhibited root penetration at all levels of watering throughout the experimental period. H. odorata seedlings still maintained a positive carbon gain at a leaf water potential as low as -3.5MPa whereas for M. elengi seedlings, photosynthesis was completely inhibited at a leaf water potential of -2.5MPa.